Brain-computer interface controlled neuromuscular electrical stimulation of the upper limb for stroke patients - Tan, Adrian Hock Guan (2011)
The human nervous system is susceptible to injury from both extrinsic and intrinsic factors such as trauma or disease. Particularly devastating injuries include stroke and spinal cord injury, where a tragically localized lesion greatly impairs motor function. Unfortunately, the central nervous system is unable to repair itself, and Man has lived with the permanent effects of paralysis, which can only be mitigated with effective rehabilitation or assistive devices. A promising method that has surfaced for stroke rehabilitation is the use of neuroprostheses, which transmits information from the brain to peripheral nerves and muscles by bypassing the damaged neural pathways.